2010
DOI: 10.1111/j.1365-2133.2010.10038.x
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib-induced epidermal growth factor receptor-independent keratinocyte apoptosis is mediated by the JNK activation pathway

Abstract: Gefitinib can induce keratinocyte apoptosis through an EGFR-independent JNK activation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…The group reversed by cetuximab is only approximately half as large as the group reversed by gefitinib, which is consistent with the lesser degree of EGFR inhibition produced by cetuximab in our model (Fig. 2), as well as with possible off target effects of gefitinib because of its inhibition of multiple kinases (49, 50). …”
Section: Resultssupporting
confidence: 89%
“…The group reversed by cetuximab is only approximately half as large as the group reversed by gefitinib, which is consistent with the lesser degree of EGFR inhibition produced by cetuximab in our model (Fig. 2), as well as with possible off target effects of gefitinib because of its inhibition of multiple kinases (49, 50). …”
Section: Resultssupporting
confidence: 89%
“…p38 MAPK pathways are known as stress response signals and interact with the PI3K/Akt/mTOR pathway [36]. Recently, it was reported that keratinocyte apoptosis induced by gefitinib, which is a selective EGFR tyrosine kinase inhibitor, is mediated by the JNK activation pathway [42]. This study did not reproduce the results of that report; therefore, the mechanisms underlying everolimus-induced keratinocyte apoptosis may differ from those underlying gefitinib-induced apoptosis.…”
Section: Discussionmentioning
confidence: 78%
“…In summary, we find that clinically available small molecule EGFR inhibitors targeting the tyrosine kinase site of the EGFR receptor, including gefitinib and lapatinib, are effective analgesics in mice for inflammatory and neuropathic pain. These drugs are routinely given to non-small cell lung cancer patients (37,38) to inhibit tumor growth, but have not been systematically studied for their role in pain management. Since we find that EREG is the primary endogenous activator of EGFR-related pain hypersensitivity, our data suggest that an effective treatment strategy may be the selective inhibition of EREG over other endogenous EGFR ligands.…”
Section: Ereg Pain Hypersensitivity Is Mediated By a Signal Transductmentioning
confidence: 99%